Penerapan Model Pembelajaran Think Pair Share untuk Meningkatkan Hasil Belajar PKn Kelas IV Sekolah Dasar - Marlina; Rahmah, Siti (IBTIDA', 2023)
The purpose of this study was to improve Civics Learning Outcomes through the Think Pair Share Learning Model of Grade Students IV of SDN Sungai Uyak Pasar Baru. This class action research was carries out in two cycles using the design Kemmis and Mc. Taggart consists of stages of planning, implementing, observing and reflecting. Data collection is by observation method and test method. Data analysis used qualitative and quantitative data analysis. The results showed that the teacher's activity in learning activities was in the first cycle of meeting 1 which was 18, the second meeting was 19 and in Cycle II, meeting 1 was 20, the second meeting was 22. The percentage of classical student activities in Cycle I meeting 1 reached 69%, the second meeting was 69%. 2 reached 76% and in the second cycle meeting 1 reached 79%, meeting 2 reached 90%. Completeness of student learning outcomes in the first cycle reached 78% and increased in the second cycle it reached 90%. Based on these findings, it can be concluded that using the Think Pair Share learning model can improve Civics learning outcomes for Grade IV Elementary School students, where this increase can be seen through learning activities using the Think Pair Share learning model which can improve the learning process, increase student activity through discussion activities and increase students' mastery of the material.